2021
DOI: 10.18388/abp.2020_5505
|View full text |Cite
|
Sign up to set email alerts
|

miR-19a-3p inhibition alleviates sepsis-induced lung injury via enhancing USP13 expression

Abstract: Sepsis is a systemic inflammatory response syndrome caused by various pathogenic microorganisms or toxins. Lung damage is one of the causes of death in patients with sepsis. This study aimed to investigate the role of miR-19a-3p and its regulation mechanism in sepsis-induced lung injury. MH-S cells were treated with lipopolysaccharide (LPS) to establish sepsis-induced lung injury cell model. C57BL/6 mice were injected with miR-19a-3p antagomiR and LPS to construct animal model. LPS-treated and control cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Herein, circ_0001498 level upregulation was detected in sepsis-related ALI patients. LPS has been used to establish sepsis-induced ALI cell model (Ren et al 2021;. Also, our experimental results demonstrated that cell viability was suppressed but apoptosis and inflammatory factors were stimulated by LPS in WI-38 cells.…”
Section: Discussionmentioning
confidence: 59%
“…Herein, circ_0001498 level upregulation was detected in sepsis-related ALI patients. LPS has been used to establish sepsis-induced ALI cell model (Ren et al 2021;. Also, our experimental results demonstrated that cell viability was suppressed but apoptosis and inflammatory factors were stimulated by LPS in WI-38 cells.…”
Section: Discussionmentioning
confidence: 59%
“…The downregulation of mir-19a-3p was found to improve inflammation and ALI induced by sepsis in both in vivo and in vitro experiments, as the reduction in pro-inflammatory cytokines demonstrated. It seems that the target gene of miR-19a-3p is represented by USP13, whose over-expression is related to amelioration and better outcomes of lung injury [ 200 ].…”
Section: Resultsmentioning
confidence: 99%
“…MiRNAs are short segments of noncoding molecules with ~22 nucleotides that can regulate cellular events by post-transcriptionally modulating their mRNAs (26). In addition, altered miRNAs has been pointed out to have roles in regulating the process of sepsis-ALI (27)(28)(29). Wang and Han (30) showed that miR-1184 was decreased in the serum of neonatal sepsis, and overexpression of miR-1184 targetedly suppressed IL-6 level to inhibit LPS-stimulated inflammatory reaction in monocytes.…”
Section: Discussionmentioning
confidence: 99%